Equity in Performance Management in Thematic Supervision of the Bolaang Mongondow Regency Local Government - Lombone, Rio A. (KnE Social Sciences, 2025)
Thematic supervision allows a comprehensive evaluation of the implementation of local government programs, including the extreme poverty alleviation program as one of the priority programs in various regions, one of which is in Bolaang Mongondow Regency. The purpose of this study was to analyze equity in performance management in thematic supervision in the regional government of Bolaang Mongondow Regency. The approach used in this research is qualitative. Data collection consisted of observation, in-depth interviews, and documentation. Primary data sources were obtained from in-depth interviews with the Inspectorate. Secondary data came from document searches. The results showed that the Inspectorate has encouraged regional apparatus to focus more on achieving key performance indicators (KPIs) relevant to extreme poverty alleviation. The extreme poverty alleviation program in Bolaang Mongondow Regency has been fairly implemented, especially towards program targets, ensuring that assistance is provided and prioritized towards vulnerable groups. The people of Bolaang Mongondow Regency, in general, feel that they have access to social assistance fairly when the process of collecting data and determining beneficiaries is carried out with transparency and participation by the OPD managing the activity. However, there are further challenges that are often faced, such as social stigma, ignorance of beneficiary criteria, and uneven distribution of assistance between sub-district and village areas.